Antioxidant Activity and Sun Protection Factor (SPF) of Various Fractions of Ethanol Extract of Kelakai Roots (Stenochlaena palustris Bedd) - Muhammad Ikhwan Rizki; Anna Khumaira Sari; Satrio Wibowo Rahmatullah (Medical Laboratory Technology Journal, 2026)
Excessive sun exposure in tropical regions can cause oxidative stress that triggers premature aging and skin cancer. Kelakai root (Stenochlaena palustris Bedd.) is a potential natural ingredient that contains various secondary metabolites with the ability as an antioxidant and sunscreen properties. This research aims to determine the antioxidant capacity and Sun Protection Factor (SPF) value of various fractions of ethanol extract of kelakai roots. Kelakai roots are washed with clean water, then dried in a drying cabinet, and then powdered. Extraction is carried out using ethanol as a solvent using a maceration method. The extract was fractionated using n-hexane, ethyl acetate, and aqueous. Phytochemical screening was performed using specific reagents. Antioxidant capacity was determined using the DPPH method based on the Inhibitory Concentration 50 (IC50) parameter. The ability as a sunscreen is measured based on the Sun Protection Factor (SPF) parameter with a UV-Vis spectrophotometer. The results of the identification of compound groups showed that the ethyl acetate fraction contained phenolic, flavonoid, tannin, alkaloid, and saponin compounds. Antioxidant testing showed that the ethyl acetate fraction had an IC50 of 16.67 ppm (very strong), followed by the aqueous fraction IC50 of 73.92 ppm (strong) and the n-hexane fraction IC50 of 95.29 ppm (strong). At the highest concentration of 500 ppm, it is known that the n-hexane, ethyl acetate, and aqueous fractions have SPF values ​​of 12.34, 34.62, and 15.71, respectively. The aqueous fraction is classified as medium protection, while the ethyl acetate fraction is classified as high protection, and n-hexane is classified as low protection. This study concluded that the ethyl acetate fraction of kelakai roots has strong potential as a source of antioxidants and natural sunscreen agents.